The Role of Green Materials and Renewable Energy, and Energy Efficiency Adoption in Driving Sustainability Performance in Agritourism Facilities - Gusain, Amit; Yadav, Monika; Badhwar, Sunita (PALASH A JOURNAL OF HOSPITALITY AND TOURISM SERVICE MANAGMENT, 2026)
Agritourism is gaining momentum as a model for sustainable rural development, yet its environmental footprint remains a pressing concern. This study examines how the adoption of green materials, renewable energy, and energy efficient technologies shapes the overall sustainability performance of agritourism facilities in India. Grounded in Environmental Management Theory and guided by the need for eco-friendly operations, the study investigates both the direct effects of these practices and the mediating role of environmental impact reduction (EIR) in improving sustainability outcomes. Data were collected from 312 valid respondents across five eco-certified agritourism farms using a standardised questionnaire. Seven hypotheses were tested using SmartPLS 4 for Partial Least Squares Structural Equation Modelling (PLS-SEM). Findings confirm that all three sustainable practices significantly reduce environmental impact, with energy efficiency demonstrating the strongest effect. Environmental impact reduction was further confirmed as a significant mediator linking each practice to overall sustainability performance. The study makes both theoretical and practical contributions. Theoretically, it positions the reduction of environmental impact as a vital intermediate mechanism in agritourism sustainability research. Practically, it equips agritourism operators, rural planners, and policymakers with evidence-based direction for prioritising green infrastructure, clean energy, and energy-efficient operations.